Candidates Cell Sources to Regenerate Alveolar Bone from Oral Tissue. (14th February 2012) - Nishimura, Masahiro; Takase, Kazuma; Suehiro, Fumio; Murata, Hiroshi
Abstract : Most of the cases of dental implant surgery, especially the bone defect extensively, are essential for alveolar ridge augmentation. As known as cell therapy exerts valuable effects on bone regeneration, numerous reports using various cells from body to regenerate bone have been published, including clinical reports. Mesenchymal cells that have osteogenic activity and have potential to be harvested from intra oral site might be a candidate cells to regenerate alveolar bone, even dentists have not been harvested the cells outside of mouth. This paper presents a summary of somatic cells in edentulous tissues which could subserve alveolar bone regeneration. The candidate tissues that might have differentiation potential as mesenchymal cells for bone regeneration are alveolar bone chip, bone marrow from alveolar bone, periosteal tissue, and gingival tissue. Understanding their phenotype consecutively will provide a rational approach for alveolar ridge augmentation.